Effect of a traditional herbal medicine, hangekobokuto, on the sensation of a lump in the throat in patients with respiratory diseases - 籠橋 克紀; 佐藤 浩昭; Kagohashi Katsunori; Tamura Tomohiro; Ohara Gen; Satoh Hiroaki (Biomedical reports, 2016)
The sensation of a lump in the throat (SLT) is not a rarely encountered symptom. The etiology of SLT appears to be multifactorial, and the psychological characteristics, stress and pressure of a psychiatric disorder may be significant factors in SLT. Hangekobokuto, one of the traditional herbal medicines, is a known drug that has an effect on SLT. The efficacy of a short‑term hangekobokuto treatment on SLT was evaluated. To assess whether a 2‑week prescription of hangekobokuto improves SLT mainly in patients with respiratory diseases, a retrospective study was performed between April 2013 and August 2015. During the study period, a total of 43 patients were treated with hangekobokuto. Twelve (27.9%) of the 43 patients were reported to experience completely effective treatment (SLT completely disappeared), and 14 (32.6%) experienced moderately effective treatment (25‑99% SLT disappeared). Patients with bronchial asthma and those without a medical history of respiratory disease exhibited a good response to hangekobokuto. No specific predictive factor of the response to hangekobokuto on SLT was identified in the multivariate regression analysis. Therefore, the present results suggested that hangekobokuto could be one of the treatment choices for uncontrolled SLT.